THE ROLE OF PT XYZ'S PORTAL TO EFFECTIVENESS OF ADMINITRATIVE ACTIVITIES IN THE CORPORATE SECRETARY ADMINISTRATION AND STRATEGIC PLANNING DIVISION OF PT XYZ JAKARTAROLE OF PT XYZ'S PORTAL TO EFFECTIVENESS OF ADMINITRATIVE ACTIVITIES IN THE CORPORATE SECRETARY - Ependi, Nur Haris (MANAGER: Journal of Management and Administration Science, 2022)
This study aims to determine the role of the PT XYZ Portal on the effectiveness of administrative activities in the Corporate Secretary and Strategic Planning Division of PT XYZ Jakarta, find out the obstacles and solutions that are made to solve the problems that occur. Data collection techniques through observation, namely observing directly the object under study. The results of the research conducted show that the PT XYZ Portal plays a major role in supporting administrative activities in the Corporate Secretary and Strategic Planning Division, this is because administrative activities can be completed in real time with the PT XYZ Portal. The obstacle that often occurs is the unreadability of employee attendance in the Employee Self Service system, which causes fatal consequences if absence correction is not carried out. For this reason, the solution is to re-check attendance in the Employee Self Service system and manually correct unread attendance for further approval by the relevant leadership.